LEADERSHIP MANAGEMENT OF THE HEAD OF PUBLIC HEALTH CENTER ( SYSTEMATIC LITERATURE REVIEW - SLR) - Herianto, Ii Puji; Tarihoran, Naf’an; Nugraha, Enung (International Journal of Multidisciplinary Research and Literature, 2025)
This study discusses the leadership management of the head of the Public Health Center (Puskesmas) through the Systematic Literature Review (SLR) approach with the PRISMA method. This study aims to investigate how the leadership style of the head of the Health Center influences the quality of health services and organizational effectiveness. The study's findings show that transformational and participative leadership help raise the health workers' job satisfaction, team coordination, and motivation. Nevertheless, the primary impediments to optimizing leadership are a variety of challenges, including a lack of managerial training, limited resources, and obstacles in policy implementation. Consequently, a strategy is required to enhance leadership capacity using ongoing training, the strengthening of data-based management systems, and policy reforms that support the effectiveness of Community Health Centers as the centre of public health services. This study offers stakeholders recommendations for enhancing leadership management in Community Health Centers to achieve more optimal health services.